Studi Kapasitas Lateral Pondasi Tiang Ujung Bebas Dengan Variasi Diameter Dan Jarak Beban Sampai Muka Tanah Pada Tanah Pasir Di Laboratorium - Arwan Apriyono (Dinamika Rekayasa, 2006)
The aim of this research is to study behavior of single free-end pile under lateral loads due to various of diameters and distance load from ground surface in cohesion less soil. The research was conducted through experimental in laboratory. Three various of diameters are: 1cm, 1.25cm and 1.5cm are used, and five various of distance load from ground surface are: 15cm, 17.5cm, 20cm, 22.5cm and 25cm. The value of ultimate lateral capacity (Pu) is determined by using interpretation method and compared to Brom's analysis method. The result of this this research is that value of the lateral capacity will increase with increasing of diameters, but it will decrease while distance load from ground surface increase.